Partisipasi Politik Masyarakat Medan Deli dalam Pemilihan Walikota di Masa Pandemi Tahun 2020 - Muhammad Ainul Hafis; Muryanto Amin; Tonny P. Situmorang (PERSPEKTIF, 2023)
The purpose of this study was to analyze the increase in voter participation during a pandemic in the Medan Deli sub-district. This is because the sub-district has the most significant surge in participation. The Medan Deli sub-district, which has the highest difference in participation when compared between the 2015 elections and the 2020 elections, is the Medan Deli sub-district. This study uses a qualitative approach with primary data collection techniques in the form of interviews with key informants, key informants and supporting informants. Then the data were also obtained from secondary sources in the form of literature relevant to the research problem. The results showed that there were five factors driving the people of Medan Deli District so that they wanted to come to participate, namely political stimulation factors, personal character factors, social character factors, situational and environmental factors and finally political education factors. Then, of the five factors, the most influential factor is the political stimulus factor that arises from daily political conversations or conversations in the community. Then later because of the candidates who came from their area, a regional spirit emerged which in the end made the people more enthusiastic to come to the TPS.